Formation factors of surface inflow to antarctic lakes of the Larsemann Hills oasis - M. R. Kuznetsova; G. V. Priakhina; S. D. Grigoreva; E. R. Kiniabaeva; М. Р. Кузнецова; Г. В. Пряхина; С. Д. Григорьева; Э. Р. Киньябаева (Arctic and Antarctic Research, 2021)
The study aims to identify formation factors of water inflow to the Antarctic lakes of the Larsemann Hills oasis (East Antarctica). The objects of study are 11 lakes of the oasis. The analysis was performed based on the expeditionary data of the Russian Antarctic Expedition (RAE): 63rd season (23 December 2017 – 3 February 2018), 64th season (12 January 2019 – 27 February 2019), 65th season (2 November 2019 – 24 March 2020). Data of lakes water level observations, aerial photography of the unmanned aerial vehicle (UAV) and route surveys are given, the results of identifying the boundaries of the lakes catchments are presented. The factors that determine the formation of water inflow to the lakes in this region were identified based on the analysis of the materials. The most significant are the meteorological conditions, the presence of perennial snowfields and glacial areas in the catchments, and the presence of lakes that can cause outburst flood. The seasonally thawed layer also has an impact on the formation of the inflow to the lakes. The vegetation cover is not so important for inflow formation in this region due to the physical and geographical conditions. As for anthropogenic activity, it mainly affects the environmental situation of the catchments and water quality, while the anthropogenic influence on the formation of water inflow to the lakes in the oasis is limited to the territories of polar stations. The factors identified should be taken into account in the further study of hydrological processes, the creation of models that describe them, and the organization of field observations. Объектами исследования являются 11 водоемов антарктического оазиса Холмы Ларсеманн. Работа выполнена по материалам сезонных работ 63 — 65-й РАЭ: используются наблюдения за уровнем воды озер, аэрофотосъемки БПЛА, маршрутные обследования, приведены результаты выделения границ водосборных площадей озер. Наиболее значимыми выявленными факторами, определяющими формирование притока воды к озерам, являются метеорологические ...